Essays on regression models for double bounded and extreme-value random variables : improved testing inferences and empirical analyses - PEREIRA, Ana Cristina Guedes (2022)
ESPINHEIRA, Patrícia Leone, também é conhecida em citações bibliográficas por: OSPINA, Patrícia Leone Espinheira.